TURLI OMILLAR TA’SIRI OSTIDAGI AKKLIMATIZATSIYANING SPORTChI ORGANIZMIGA TA’SIRI - Ernazarov, Gʻ.N.; To‘xtasinova, Z.M. (SCIENCE and SOCIETY, 2025)
The article examines in detail the process of acclimatization of athletes to various geographical conditions. Short-term and long-term types of acclimatization are described, and examples of improved results are given of Uzbek athletes thanks to training in mountainous areas.
Keywords: acclimatization; sports physiology; adaptation to altitude; erythrocytes; training in the mountains